Brand Image Tokopedia pada Kampanye Public Relation #BangkitBersama Pasca Pandemi Covid-19 - Afni Madalinna Haidara (Ultimacomm: Jurnal Ilmu Komunikasi, 2022)
After the Covid-19 pandemic, various industrial sectors were affected by the Covid-19 outbreak, including Tokopedia. Tokopedia is a technology-based trading company or electronic commerce (e-commerce). Public relations (PR) has an important role in managing the crisis experienced by the company. Through the #BangkitBersama campaign, Tokopedia believes that with the spirit of gotong royong, Indonesia can rise together after the Covid-19 pandemic. The #BangkitBersama campaign will create associations or perceptions of Tokopedia. So, through this research, researchers want to know Tokopedia's brand image from a consumer perspective in the #BangkitBersama public relations campaign after the Covid-19 pandemic. This study uses a descriptive qualitative approach with a case study method. Data were collected by conducting interviews with five sources who were exposed to the #BangkitBersama campaign, observations, and document or literature studies. The results showed that through the #BangkitBersama campaign the perception of togetherness and cooperation emerged in the minds of consumers. The #BangkitBersama campaign has succeeded in generating a positive image for Tokopedia and maintaining the loyalty of Tokopedia users. Keywords: Brand Image, Campaign, Public Relations, Covid19, Tokopedia